Sustainability and organizational design in informal groups, with some evidence from Kenyan roscas - Siwan Anderson; Jean-Marie Baland; Karl Ove Moene (University of Oslo, Department of Economics, 2003)
Informal groups cannot rely on external enforcement to insure that members abide by their obligations. It is generally assumed that these problems are solved by social sanctions and reputational effects. The present paper focuses on roscas, one of the most commonly found informal financial institutions in the developing world. We first show that, in the absence of an external (social) sanctioning mechanism, roscas are never sustainable, even if the defecting member is excluded from all future roscas. We then argue that the organizational structure of the rosca itself can be designed so as to reduce the severity of enforcement issues. The implications of our analysis are tested against first-hand evidence from rosca groups in a Kenyan slum.
Keywords: G20; 330; Roscas; informal financial institutions; developing world; Informeller Finanzsektor; Kenia